2015
DOI: 10.1109/tnet.2014.2310815
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Medium Access Protocol: Throughput and Short-Term Fairness Perspective

Abstract: We consider a simple MAC protocol, called the renewal access protocol (RAP), that adopts all of the legacy 802.11 standard but the backoff stage feature. To meet two objectives in the design of the RAP-optimal throughput and high short-term fairness-we develop a mathematical model of the RAP and rigorously analyze the performance of the RAP. First, we show that the throughput performance of the RAP depends only on the expectation of the selection distribution where the backoff counter is selected, provided tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…In the above, E [B s ] and E [B c ] are the average lengths of time periods for a successful packet transmission and a collided packet transmission, respectively. They are derived in the same way as given in Bianchi (2000), Bianchi et al (1996) as follows: It is shown in Kim and Hwang (2015) that throughput T in (2) is a strictly convex function of τ . Since τ depends only on μ, we conclude that the network throughput performance depends only on the first moment (expectation) of the selection distribution, which is in accordance with well-known results in earlier works, e.g., Kumar et al (2007).…”
Section: Throughput Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the above, E [B s ] and E [B c ] are the average lengths of time periods for a successful packet transmission and a collided packet transmission, respectively. They are derived in the same way as given in Bianchi (2000), Bianchi et al (1996) as follows: It is shown in Kim and Hwang (2015) that throughput T in (2) is a strictly convex function of τ . Since τ depends only on μ, we conclude that the network throughput performance depends only on the first moment (expectation) of the selection distribution, which is in accordance with well-known results in earlier works, e.g., Kumar et al (2007).…”
Section: Throughput Analysismentioning
confidence: 99%
“…To consider the fairness of the protocol itself, we assume that there are no hidden or exposed terminals and each terminal transmits packets of the same size. The analysis in short-term fairness in Kim and Hwang (2015) is summarized below. We will use the same notations as given below in the delay analysis.…”
Section: Short-term Fairness Analysismentioning
confidence: 99%
See 3 more Smart Citations